2006
DOI: 10.1243/1464419jmbd13
|View full text |Cite
|
Sign up to set email alerts
|

Some characteristics of rolling-element bearings under oscillating conditions. Part 2: Experimental results for interference-fitted taper-roller bearings

Abstract: Some stiffness and damping characteristics are presented for taper-roller bearings with interference fits. The major parameters investigated were preload, temperature, lubricant viscosity, excitation frequency, excitation amplitude, and rotational speed. The prediction, based on a model of the bearings, that stiffness and damping would effectively be independent of oil viscosity was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…The speed of rotation and the preload on the bearing(s) may also affect the characteristics. Some early work, published in a restricted circulation [11], was made more widely known [12][13][14]. This showed that the damping in rolling element bearings was not negligible and that there was also damping in the necessary interface between the outer race of the bearing and its housing.…”
Section: Radial and Tilt Characteristics Of Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed of rotation and the preload on the bearing(s) may also affect the characteristics. Some early work, published in a restricted circulation [11], was made more widely known [12][13][14]. This showed that the damping in rolling element bearings was not negligible and that there was also damping in the necessary interface between the outer race of the bearing and its housing.…”
Section: Radial and Tilt Characteristics Of Bearingsmentioning
confidence: 99%
“…It is appropriate to describe the method used for the measurements as they were achieved in a reasonably direct manner. The initial work was that of Walford [15], Walford and Stone [16][17][18] and extended by Lambert et al [12][13][14].…”
Section: Radial and Tilt Characteristics Of Bearingsmentioning
confidence: 99%
“…The effect of joints was investigated by constructing another rig identical to that described in parts 1 and 2 [2,3] of this paper, but with a nominal clearance fit of 5/10 mm between the outer races and the housing. The inner race was again interference fitted so that the joint stiffness would be largely governed by the outer joint and it was possible, if necessary, to measure any deflection occurring across this joint.…”
Section: Taper-roller Rig With a Clearance Fitmentioning
confidence: 99%
“…It was again not possible to establish an absolute reference for the preload but the two preloads tested were of nominally 10 and 40 mm axial preset displacement. These preloads correspond to the light and heavy preloads of the initial rig [3]. The instrumentation, calibration, and experimental methods were as described in references [2,3].…”
Section: Taper-roller Rig With a Clearance Fitmentioning
confidence: 99%
See 1 more Smart Citation